SEVERE FORM OF CROHN’S DISEASE IN COMBINATION WITH AUTOIMMUNE LIVER DISEASE - G. I. Sinenchenko; S. S. Gaiduk; M. I. Gromov; A. V. Kosachev; L. P. Pivovarova (Вестник хирургии имени И.И. Грекова)
The proven data on the dangerous using of drugs from the group of monoclonal antibodies to TNF-alpha in patients with Crohn’s disease, as well as methods of correction of the revealed homeostasis disorders are pre- sented.